Rapid warming and degradation of mountain permafrost in Norway and Iceland - B. Etzelmüller; K. Isaksen; J. Czekirda; S. Westermann; C. Hilbich; C. Hauck (The Cryosphere, 2023)
With the EU-funded PACE (Permafrost and Climate in Europe) project at the turn of this century, several deep boreholes (100 m+) were drilled in European mountain sites, including in mainland Norway, Svalbard and Sweden. During other projects from 2004 and the International Polar Year (IPY) period in 2006–2007, several additional boreholes were drilled in different sites in both Norway and Iceland, measuring temperatures along both altitudinal and latitudinal gradients. At most sites, multi-temporal geophysical soundings are available using electrical resistivity tomography (ERT). Here, we study the development of permafrost and ground temperatures in mainland Norway and Iceland based on these data sets. We document that permafrost in Norway and Iceland is warming at a high rate, including the development of taliks in both Norway and Iceland in response to global climate change during the last 20 years. At most sites, ground surface temperature (GST) is apparently increasing more strongly than surface air temperature (SAT). Changing snow conditions appear to be the most important factor for the higher GST rates. Modelling exercises also indicate that the talik development can be explained by both higher air temperatures and increasing snow depth.